Synthesis of 4-Substituted Aroyloxymethylcarbonyl-3-Methyl- Substituted Phenyl-6-Imino-4,7-Dihydro-1,3-Thiazino (5,4-d) Pyrazolones as Antihistaminic Agents - Kudari, S.M.; Sajjanshetty, A.S. (Asian Journal of Chemistry, 2012)
Reaction of substituted aroyloxy acid hydrazide (1a-c) with ethylacetate gave the corresponding 4-substituted aroyloxymethylcarbonyl-3-methyl-∆2-pyrazolin-5-one (2a-c) in good yields. Condensatin of (2a-c) with different aryl aldehydes under Knoevenagal conditions furnished 4-substituted aroyloxymethyl carbonyl-4-arylideno-3-methyl-5-pyrazolone (3a-e). These on refluxing with thiourea and potassium hydroxide gave 4-substiuted aroyloxymthyl carbonyl-3-methyl-substitued phenyl-6-imino-4,7-dihydro-1,3-thiazino-(5,4-d)-pyrazolone (4a-e). Few 5-pyrazolones were screened for antihistaminic activity against ileum portion of an adult guinea pig.